Biological and Bioinspired Inorganic N-N Bond-Forming Reactions - Ferousi, Christina; Majer, Sean H; DiMucci, Ida M; Lancaster, Kyle M (Chemical reviews, 2020)
The metallobiochemistry underlying the formation of the inorganic N-N-bond-containing molecules nitrous oxide (N O), dinitrogen (N ), and hydrazine (N H ) is essential to the lifestyles of diverse organisms. Similar reactions hold promise as means to use N-based fuels as alternative carbon-free energy sources. This review discusses research efforts to understand the mechanisms underlying biological N-N bond formation in primary metabolism and how the associated reactions are tied to energy transduction and organismal survival. These efforts comprise studies of both natural and engineered metalloenzymes as well as synthetic model complexes.